Kecerdasan Emosi Mahasiswi Bercadar Serta Implikasinya Bagi Pelayanan Bimbingan dan Konseling di Perguruan Tinggi - Rizky Andana Pohan; Dika Sahputra (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2020)
This study aims to determine the emotional intelligence of female students who wear the full face veil. This research uses a quantitative approach with descriptive methods. The sampling technique was carried out with a total sampling of 38 students who wore the veil from several universities in Indonesia. The research instrument uses a Likert-shaped Emotional Intelligence Scale owned by Dika Sahputra. Questionnaires are distributed online through the Google Forms application from November 2019 to January 2020. The results showed that in general the emotional intelligence of students who wore the full face veil was in the high category. These results can be used as a basis for making programs for guidance and counseling services in tertiary institutions, as well as being the basis for policy making for university leaders and the government towards female students and women who use the full face veil